Succinyl-CoA:3-ketoacid CoA transferase (SCOT) deficiency presenting as ketosis with hyperglycemia: A case report - Anupam Bahe (Wolters Kluwer Medknow Publications, 2022)
We describe a case of previously normal 22-month-old male who presented with vomiting, loose motions, lethargy, and seizures for 1 day. He had high anion gap metabolic acidosis, hyperglycemia, and ketosis managed elsewhere as diabetic ketoacidosis. Early management included hemodynamic stabilization, mechanical ventilation, correction of metabolic acidosis, seizure control, and later peritoneal dialysis. He was finally diagnosed with succinyl CoA 3 ketoacid transferase deficiency, a disorder of ketone metabolism usually presents with metabolic acidosis, ketosis, and hypoglycemia. Most cases present during the neonatal period (50%) and remain up to 20 months of age. The pathognomic finding is a nonspecific elevation on ketones in urine gas chromatography-mass spectrometry. Genomic sequencing is confirmatory.